Podmioty pozarządowe w global governance - Fel, Stanisław (MITEL, 2006)
Autor przedstawia główne etapy powstawania i rozwoju globalnego zarządzania. Nakreśla wielorakie i różnorodne sposoby jej rozumienia, często pomijane w: refleksja nad globalizacją. Po wykazaniu przykładów opisowego/analitycznego uważa je za niewystarczające i uzupełnia je o podejście polityczno-strategiczne. Wskazuje, że konieczne jest uwzględnienie etycznego aspektu globalizacji”. procesy. Następnie status organizacji społeczeństwa obywatelskiego i sektora prywatnego gospodarki w ramach tych procesów. W podsumowaniu artykułu Autor przygląda się zarówno słabym, jak i mocnym stronom dotychczasowej działalności organizacji pozarządowych w sferze globalizacji.

The author presents major stages of the origin and development of global governance. He outlines a multiple and diverse way of its understanding which is often overlooked in the reflection on globalization. Having demonstrated examples of a descriptive/analytical concept, he regards them as insufficient and supplements them by a political/strategic approach. He indicates that it is necessary to include an ethical aspect of the globalization processes. Then the status of the civic society organizations and those of the private sector of the economy within those processes are presented. In the conclusion of the paper the author looks at both weak and strong sides of the current activity of non-governmental organizations in the sphere of globalization.
Non-Governmental Subjects in Global Governance